2019
DOI: 10.3390/su11184872
|View full text |Cite
|
Sign up to set email alerts
|

Policy Evolution in the Chinese PPP Market: The Shifting Strategies of Governmental Support Measures

Abstract: Much attention has been paid world-wide to the advancement of policy with regard to public–private partnerships (PPPs). Though PPPs continue to play a major role in the development of China’s national economy, capital projects and infrastructure upgrade, little work has been done to understand the evolution of Chinese governmental policy with regard to PPPs. This paper addresses this lack and sets out the trajectory of Chinese PPP policy maturation over the period of 1986 to 2018. Policy documents were retriev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…For PPP projects, the influence of the legal system environment on government trust decision-making of the private sector is moderate, with a path coefficient of 0.68. Guo et al (2019) suggested that the legal environment affects the generation of trust, which is similar to the result of this paper. In the institutional environment of PPP projects, the perfection of relevant laws, regulations and supervision mechanisms occupies a very important position because they determine whether the project has a stable political and economic environment (Song et al , 2013).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For PPP projects, the influence of the legal system environment on government trust decision-making of the private sector is moderate, with a path coefficient of 0.68. Guo et al (2019) suggested that the legal environment affects the generation of trust, which is similar to the result of this paper. In the institutional environment of PPP projects, the perfection of relevant laws, regulations and supervision mechanisms occupies a very important position because they determine whether the project has a stable political and economic environment (Song et al , 2013).…”
Section: Discussionsupporting
confidence: 86%
“…Osei-Kyei and Chan ( 2016) pointed out that PPP policy is one of the key factors for the success of public-private cooperation, and the effectiveness of PPP projects is influenced by the legal system environment and political background. At present, there are still some problems in the legal system environment of PPP project construction in China, including the lack of policy coordination among departments, the lack of financial incentives and the weak supervision of transparency and information disclosure (Guo et al, 2019). The absence of strong institutional guarantees restricts the government's trust in the private sector.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is confirmed by Guo, Martek and Chuan (2019:2), who indicated that 'more than 90% of PPP projects were initiated by local governments in China'. The prevalence of PPPs at the local level is attributed to the introduction of a policy titled 'Opinions on strengthening the management of local government debt', which allowed for meaningful private sector participation in urban infrastructure through franchise and other options (Guo et al 2019).…”
Section: Trends In the Public-private Partnership Practices Of The Br...mentioning
confidence: 99%
“…However, the neglect of certain special features in Chinese PPP projects was a downside. Such features included PPP initiators' identity and payment mechanism [5,6]. In a previous study, more than 90% of PPP projects were reported to be initiated by local governments; moreover, government payment was adopted in 34% of PPP projects [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the rapid development of PPP in China, the ways to finance and promote the implementation of projects are receiving an increasing amount of attention [6]. It is difficult for PPP projects to obtain support from financing institutions because of the large investment, low profitability and unstable cash flow [7].…”
Section: Introductionmentioning
confidence: 99%